The Trade-Based Diversion of Three-Kilogram LPG Subsidies: A Contemporary Islamic Legal Perspective on Justice and Equity - Dahyul Daipon; Miswardi; Saiful Amin; Mhd Asyraful Badri; Hoirol Anuar Mak Din (MILRev: Metro Islamic Law Review, 2025)
This article explores the phenomenon of misappropriation in the distribution of three-kilogram subsidized LPG through trade practices in West Sumatra, analyzed from the perspective of the Islamic law that focuses on the principles of justice (‘adl) and trustworthiness (amanah). The study also examines the mechanisms through which subsidized LPG diversion occurs in trade and how Islamic legal principles interpret such practices, particularly in the context of subsidy distribution inequality. A qualitative approach with a descriptive method was employed in this research. Primary data were collected through field observations and structured interviews with 20 sellers and 10 buyers directly involved in the trade of subsidized LPG. Secondary data were sourced from academic journals, scholarly articles, and policy reports concerning energy subsidy distribution. The findings reveal that the trade of subsidized LPG is driven by weak regulatory oversight, unequal distribution channels, and the widespread use of social media platforms for transactions. As a result, subsidies intended for low-income communities are often diverted to middle- and upper-income groups, exacerbating social inequality and increasing the economic burden on vulnerable populations. From an Islamic legal perspective, such practices violate the principles of justice and trustworthiness and may be classified as ghasab—the unlawful seizure of others’ rights. Therefore, the study emphasizes the urgent need for reform in the subsidized LPG distribution system through improved oversight, the utilization of digital technology, and public education on the importance of maintaining trust in state-subsidized resources.